Illegitimate Offspring in Montenegro at the Beginning of the 20th Century - Kulauzov, Maša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
The article sheds light on Montenegrin legislature regarding out-of-wedlock infants, particularly on Law on illegitimate children of 1894, whose author, famous jurist Valtazar Bogišić had put significant effort into protecting this vulnerable social group. His successor on the position of minister of justice Lujo Vojnović also had understanding for sensitive and fragile status of illegitimate offspring, so he issued necessary bylaws in which he more precisely defined distribution of the illegitimate childrenʹs trust assets to beneficiaries. On the other hand, the Supreme Court also passed some decrees regarding children born outside of marriage that were addressed to district courts and local authorities. All aforementioned documents were carefully scrutinized in this paper, as well as chapters XVI-XVIII of Criminal code for the Principality of Montenegro from 1906. The Code thoroughly regulated neonaticide (killing of an infant within the first 24 hours of birth), abandonment of illegitimate newborns, unlawful termination of pregnancy, as well as all kinds of accomplices in these crimes in order to protect lives of illegitimate children.